Implementation Of The Health Equipment Maintenance Management System At The Maintenance Installation Of Facilities And Infrastructure Of The Medical Hospital, Bogor City Regional Hospital In 2024 - Bassuni, Wahyu; Dewi, Mira; Inkiriwang, Corrie Mary Milka; Pakpahan, Marisi; Mausul, Ahmad (LPPM Universitas PGRI Sumatera Barat, 2023)
This study discusses the implementation of a medical equipment maintenance management system in the Medical Facilities Maintenance Installation (IPSRS Medis) of RSUD Kota Bogor. This study underlines the important role of medical equipment maintenance to ensure efficient hospital operations and minimize the risk of equipment failure, which can have a negative impact on the quality of health services. This study aims to evaluate the availability of human resources, budget, and supporting facilities required for effective medical equipment maintenance. A qualitative research approach was adopted, combining data collection methods such as observation, interviews, and documentation analysis. The findings of the study revealed that the implementation of a maintenance management system in RSUD Kota Bogor has not been fully effective. Several challenges still exist, including a lack of skilled human resources, budget constraints, and inadequate supporting facilities. This study suggests increasing the quantity and skill level of human resources, improving budget planning, and strengthening the monitoring and evaluation system to ensure that medical equipment operates consistently. It is hoped that these insights will provide valuable guidance for the management of medical equipment in hospitals and contribute to improving the quality of health services in RSUD Kota Bogor.